PEMAHAMAN MULTIKULTURAL MELALUI BIMBINGAN KELOMPOK BAGI FORUM ANAK DESA - Firdaus, Azzahro; Khusumadewi, Ari; Purwoko, Budi; Winingsih, Evi (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2024)
Abstract: Multicultural, as cultural diversity, One of the important issues needed for the Village Children's Forum is multicultural understanding. This research aims to determine the success of using Group Guidance services in providing an understanding of multiculturalism for the Village Children's Forum. This research uses the Systematic Literature Review (SLR) method using PRISMA (Preferred Reporting Items For Systematic Reviews And Meta Analyses) guidelines. A total of 7 journals in the period 2019 - 2024 used Google Scholar with the keywords "multicultural and group guidance". The results of the research state that group guidance using group discussion techniques can provide multicultural understanding to children so that they have a tolerant character. The conclusion of this research shows that multicultural understanding is a foundation for creating harmony and developing positive behavior for the Village Children's Forum through group guidance services by utilizing group dynamics.Abstrak: Multikultural, sebagai keberagaman budaya, Salah satu isu penting yang dibutuhkan bagi Forum Anak Desa adalah pemahaman multikultural. Penelitian ini bertujuan untuk mengetahui keberhasilan dalam penggunaan layanan Bimbingan Kelompok dalam memberikan pemahaman tentang multikultural Bagi Forum Anak Desa. Penelitian ini menggunkan metode Systematic Literature Review (SLR) dengan menggunakan pedoman PRISMA (Preferred Reporting Items For Systematic Reviews And Meta Analyses). Sebanyak 7 jurnal dalam rentang tahun 2019 - 2024 menggunakan google scholar dengan kata kunci “multikultural dan bimbingan kelompok”. Hasil penelitian menyatakan bahwa bimbingan kelompok dengan teknik diskusi kelompok dapat memberikan pemahaman multikultura kepada anak agar memiliki karakter toleransi. Kesimpulan dari penelitian ini menunjukkan bahwa pemahaman multikultural menjadi sebuah pondasi untuk menciptakan keharmonisan dan mengembangkan perilaku positif bagi Forum Anak Desa melalui layanan bimbingan kelompok dengan memanfaatkan dinamika kelompok.